CHILD’S BILE TRACT ATHERIA: DIAGNOSIS AND TREATMENT PROBLEMS. - Suvonkulov Uktam Toirovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Biliary tract atresia (BAT) in children is a rare but serious disease that leads to impaired bile outflow from the liver and often causes chronic liver failure. The article examines modern approaches to the diagnosis and treatment of ARF, including the use of ultrasound and cholangiography to confirm the diagnosis, as well as surgical intervention (Kasaya’s surgery) as the primary treatment method. Long-term treatment outcomes and the prospects of new methods, such as gene therapy and the use of stem cells, are also analyzed. Data from Google Scientific, Scopus, and other scientific databases were used to present current information on biliary tract diseases. The article emphasizes the need for early diagnosis and timely intervention to improve the prognosis and quality of life of children with ASD.